Inovasi Proses Kreatif Rosette Guitar Quartet Di Era New Normal - Fikri, Kanzul (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2021)
Rosette guitar quartet is a guitar quartet group consisting of four guitar players and on originally the Rosette guitar quartet was performing classical guitar songs arranged in four guitars. Method in this research using an qualitative approach. Qualitative research tries to answer question rather than testing the hypothesis. This research uses creative process theory and innovations theory which consist of 4 types, namely (1) Discovery (2) Extension (3) Duplication (4) Synthesis. The Result of innovation made by Rosette guitar quartet are (1) Invention made by Rosette Guitar is creating a new process in the guitar quartet group perfoming songs in postmodern era and uploaded on social media, such as â€œYoutubeâ€, (2) Development of the Rosette guitar expresses his works in social media, where to adjust the new habits to music enthusiast that can appreciate perfoming of Rosette by virtual. (3) Rosette Guitar duplicate the most successful musicians used to express and maximize each his work in â€œYoutubeâ€ which gets a lot of appreciation (viewers) according to the new normal era. (4) The Rosette guitar perfoms synthesis with create new works every month and uploaded on â€œYoutubeâ€. Collaborative creative process of this synthesis considered by Rosette guitar quartet as great opportunity to music works, expression as well as new innovations in industry creative in the new normal era.Keywords: Innovation, Creative Process, New Normal.